New records of the genus Clistopyga Gravenhorst, 1829 (Hymenoptera: Ichneumonidae: Pimplinae) from the Oriental region, with description of a new species - Varga, Oleksandr; Reshchikov, Alexey (Zootaxa, 2015)
A new species, Clystopyga longifemoralis Varga & Reshchikov sp. n., is described and illustrated from Thailand. Clistopyga latifrontalis (Uchida, 1941) is re-described and illustrated. Clistopyga nagatomii Kusigemati, 1984 is considered to be a junior synonym of C. sziladyi Kiss, 1959 (syn. nov) and also recorded from India for the first time.